Helicobacter pylori chemoreceptor TlpC mediates chemotaxis to lactate - Mayra A. Machuca (Nature Portfolio, 2017)
Abstract It is recently appreciated that many bacterial chemoreceptors have ligand-binding domains (LBD) of the dCACHE family, a structure with two PAS-like subdomains, one membrane-proximal and the other membrane-distal. Previous studies had implicated only the membrane-distal subdomain in ligand recognition. Here, we report the 2.2 Å resolution crystal structure of dCACHE LBD of the Helicobacter pylori chemoreceptor TlpC. H. pylori tlpC mutants are outcompeted by wild type during stomach colonisation, but no ligands had been mapped to this receptor. The TlpC dCACHE LBD has two PAS-like subdomains, as predicted. The membrane-distal one possesses a long groove instead of a small, well-defined pocket. The membrane-proximal subdomain, in contrast, had a well-delineated pocket with a small molecule that we identified as lactate. We confirmed that amino acid residues making contact with the ligand in the crystal structure—N213, I218 and Y285 and Y249—were required for lactate binding. We determined that lactate is an H. pylori chemoattractant that is sensed via TlpC with a K D = 155 µM. Lactate is utilised by H. pylori, and our work suggests that this pathogen seeks out lactate using chemotaxis. Furthermore, our work suggests that dCACHE domain proteins can utilise both subdomains for ligand recognition.